Introducing a New Technology for Seawater Treatment With Solar Energy - El-Hadad, Omar (2013)
Solar desalination has been used for long time to obtain potable water from seawater, but because of a number of technical difficulties, the technique has not been commercialized to serve industrial-scale or large communities demand of water. With the current trend of population increase in the world (and in South-East Asia in particular), affordable water desalination techniques will be highly required, as most current techniques, including those using distillation or membranes, have high initial and running costs. The technique suggested here will significantly reduce the running cost of water desalination units. With a simple distillation process requiring only solar energy to evaporate the water, this technique will introduce, for the first time, a practical way to desalinate seawater at a significantly low running cost. Successful implementation of this technique will be of good value to the economies of countries are exposed to sunshine for long hours per day or year, most valuable incorporation of this technique is expected to be in countries of the equatorial region having long coasts.